Preference of Generation Z in Choosing Coffee Shops in Penelokan, Kintamani - I Wayan Pradnya Baskara; Ni Wayan Pastini; I Gusti Agung Febrianto (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2025)
Purpose: This study aims to examine the preferences of Generation Z in selecting coffee shops in Penelokan, Kintamani, a popular tourism village in Bangli Regency, Bali, known for its scenic views of Lake and Mount Batur. Understanding these preferences is essential for coffee shop owners operating in this highly competitive and rapidly growing area. Method: The research employs a descriptive quantitative approach supported by qualitative data. Data were collected through questionnaires, interviews, and documentation. A total of 50 Generation Z respondents were selected using Hair’s sampling rule. The data were analyzed using mean scores for each attribute and subsequently classified into preference categories based on predetermined intervals. Result: The findings reveal that Generation Z considers atmosphere (mean = 4.54), product quality (mean = 4.41), and service (mean = 4.24) as very important factors in choosing a coffee shop. In contrast, price (mean = 4.20) and facilities (mean = 4.12) are assessed as important factors. Overall, the results indicate that experiential and aesthetic aspects, supported by good product quality and service, are central to Generation Z’s coffee shop preferences in Penelokan. Contribution: This study contributes to the literature on consumer behavior and coffee shop management in tourism destinations by providing empirical evidence on Generation Z’s preference structure. Practically, the findings offer guidance for coffee shop owners and managers in Penelokan, Kintamani to prioritize atmosphere, product quality, and service quality in their value propositions, while strategically managing pricing and facilities to better align with the expectations of Generation Z consumers.